2019
DOI: 10.1158/1538-7445.am2019-2383
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2383: The molecular binding mechanism of tislelizumab, an investigational anti-PD-1 antibody, is differentiated from pembrolizumab and nivolumab

Abstract: Programmed cell death protein 1 (PD-1) is an immune checkpoint receptor expressed by activated T, B, and NK cells, which interacts with its ligand PD-L1/L2 to inhibit T-cell proliferation and effector functions such as tumor cell killing and cytokine production. Two anti-PD-1 antibodies approved by the FDA, pembrolizumab and nivolumab, have shown efficacy in many cancer types, nevertheless there are some indications where limited efficacy is observed. Tislelizumab (BGB-A317), an investigational anti-PD-1 antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Tislelizumab is a monoclonal antibody with high affinity and specificity for PD-1 that was specifically engineered to minimize FcɣR binding on macrophages, thereby abrogating antibody-dependent phagocytosis, a potential mechanism of T-cell clearance and resistance to anti-PD-1 therapy [19]. Tislelizumab has shown higher affinity to PD-1 than pembrolizumab and nivolumab with an approximately 100and 50-fold slower off-rate, respectively [20]. Moreover, tislelizumab has a different binding orientation to PD-1 compared with pembrolizumab and nivolumab.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tislelizumab is a monoclonal antibody with high affinity and specificity for PD-1 that was specifically engineered to minimize FcɣR binding on macrophages, thereby abrogating antibody-dependent phagocytosis, a potential mechanism of T-cell clearance and resistance to anti-PD-1 therapy [19]. Tislelizumab has shown higher affinity to PD-1 than pembrolizumab and nivolumab with an approximately 100and 50-fold slower off-rate, respectively [20]. Moreover, tislelizumab has a different binding orientation to PD-1 compared with pembrolizumab and nivolumab.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tislelizumab has a different binding orientation to PD-1 compared with pembrolizumab and nivolumab. While the binding surface on PD-1 for tislelizumab partially overlaps with that for pembrolizumab, it significantly differs from that for nivolumab [20]. In two early phase studies, single-agent tislelizumab (200 mg) administered intravenously (IV) every 3 weeks (Q3W) was generally well tolerated and showed antitumor activity in both Caucasian and Asian patients [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Tislelizumab is a humanized monoclonal antibody (mAb) with high affinity and specificity for PD-1 that was engineered to minimize binding to FcgR on macrophages to greatly reduce antibodydependent phagocytosis, a potential mechanism of T-cell clearance and resistance to anti-PD-1 therapy (19). Using structure-guided mutagenesis and Biacore studies, tislelizumab has been found to be structurally differentiated from both pembrolizumab and nivolumab by its unique binding epitopes and binding kinetics (20). In two earlyphase studies (NCT02407990, CTR20160872), tislelizumab (200 mg) administered intravenously every 3 weeks (Q3W) was generally well tolerated and demonstrated promising antitumor activity in both Asian and non-Asian patients with advanced solid tumors, including EC and GC (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Tislelizumab has a different binding orientation to PD-1 versus pembrolizumab and nivolumab; the binding surface on PD-1 for tislelizumab partially overlaps with that for pembrolizumab but differs significantly from that for nivolumab [33]. With a disassociation constant (K D ) of 0.15 nmol/L, tislelizumab binds to Gln75, Thr76, Asp77, and Arg86 of human PD-1 with high specificity and affinity [33,34].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Nivolumab and pembrolizumab do not require these epitopes to bind and have faster dissociation rates than tislelizumab. Tislelizumab has shown an approximately 50-fold and 100-fold slower dissociation rate compared with nivolumab and pembrolizumab, respectively [33]. Studies with pembrolizumab and nivolumab have demonstrated that maximal receptor occupancy on circulating CD3 + T cells occurs at concentrations that are much lower than the clinical dose for nivolumab and pembrolizumab [35,36].…”
Section: Pharmacodynamicsmentioning
confidence: 99%